Assessment of Corrosion Inhibition Efficiency of Some Amino Acids on Stainless Steel in Ethaline - Ahmed, Essa I.; Abdallah, Hassan H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This study evaluates simple amino acids as green corrosion inhibitors for AISI 302 stainless steel in Ethaline, a chloride-rich deep eutectic solvent (DES). General and localized corrosion behaviors were assessed using Tafel analysis and cyclic potentiodynamic polarization (CPP) in blank Ethaline and with 0.05 M, 0.075 M, and 0.1 M glycine, alanine, and leucine.​ Results show complex interactions between amino acid structure, concentration, and inhibition. The high viscosity of Ethaline shifts anodic control from charge transfer to mass transfer at higher potentials. All amino acids shift corrosion potential (Ecorr) nobly, with 0.05 M glycine giving the largest increase ( 0.26 V) for general corrosion resistance, though it yields the narrowest passivation range (0.52 V), increasing pitting susceptibility. Alanine and leucine, with bulkier side chains, enhance localized corrosion resistance via steric hindrance to Cl⁻ ions.​ Low concentrations (0.05 M) optimize protection by lowering passivation current (ipass) and forming stable films, but higher levels (>0.05 M for glycine/leucine) reverse this, accelerating corrosion via acidity or complexation. A 0.05 M glycine/leucine binary mixture produces negative CPP hysteresis, indicating strong repassivation and self-healing.​ These findings reveal trade-offs between general and localized protection, emphasizing precise concentration control. The study advances tailored, synergistic amino acid inhibitors as sustainable, self-healing systems for DES environments.